Advanced Renal-Cell Carcinoma Pseudoprogression After Combined Immunotherapy: Case Report and Literature Review - Zhang, Xiaojie; Huang, Hao; Han, Lu; Li, Tiepeng; Wang, Zibing; Gao, Quanli (Frontiers in Oncology, 2021)
Treatment with a combination of programmed cell death-1 (PD-1) blocker and cytokine-induced killer (CIK) cells has improved outcome in cancer patients but is also associated with various patterns of responses. Pseudoprogression is a unique and uncommon phenomenon with no clear criteria for rapid diagnosis. Although some reports of pseudoprogression during immunotherapy exist, there are few reports of pseudoprogression occurring twice in the same patient. Here, we report the case of 51-year-old female patient with advanced renal cell carcinoma, who received a combination treatment of PD-1 blocker and CIK cells, and where pseudoprogression of lung and brain tumors occurred successively during treatment.